A CARBONATE RAMP EVOLUTION IN THE TRANSITION FROM THE APULIA PLATFORM TO THE IONIAN BASIN DURING EARLY TO LATE CRETACEOUS (NW GREECE) - Getsos, K.; Pomoni-Papaioannou, F.; Zelilidis, A. (Bulletin of the Geological Society of Greece, 2007)
Facies analysis of Cretaceous carbonate sequences from the external and central Ionian zone revealed a homoclinal ramp model of evolution. During Berriasian to Valanginian, the carbonate ramp was differentiated to an inner-mid and outer ramp environment, which corresponded to the external and central Ionian zone, respectively, while the main inner ramp environment is assumed that was located in the Pre-Apulian zone. The external Ionian zone (inner-mid ramp) is characterized by muds tones-wackes tones with fragmented echinoderms, bivalves, radiolarians and rare aptychus considered to be deposited below the fairweather wave base (FWWB). Locally, thin graded storm deposits intervene, indicating deposition above the storm weather wave base (SWB). Minor occurrences of packs tonesgrainstones, with fragmented echinoderms, calcareous algae, tubiphytes, lagenid foraminifera and rare ooids occur, as well, considered to be deposited at the lowermost part of the inner ramp, near the constantly agitated fairweather wave base (FWWB). The central Ionian zone (outer ramp) is mainly characterized by mudstones-wackestones with abundant radiolarians and rare calpionellids and calcispheres, considered to be deposited below the storm wave base (SWB). No talus or breccias deposits were observed, during the mentioned time interval, in any part of the studied area. From Hauterivian to Turonian, continual sea-level rise, led to establishment of outer ramp environment in the external Ionian zone, over the previous inner-mid ramp, and outer ramp-basin environment, over the previous outer ramp, in the central Ionian zone. The transition from shallower to deeper conditions is characterized by an overall deposition of mudstones-wackestones with abundant radiolarians rooted in pure micrite.